Homelessness in California - Economic causes - Jakubišin, Marek (2025)
This thesis examines economic factors contributing to homelessness in the US with a focus on California, specifically housing costs, income inequality, rent burden, housing availability, and regulatory issues. By comparing California with New York and Florida, states with comparable populations and income inequality levels, the study mainly utilizes data from 2010 to 2023 from the U.S. Census Bureau and the Department of Housing and Urban Development. The analysis explores how these economic elements and regulatory frameworks interact differently across states, impacting homelessness.